PENGGUNAAN KARTU KUARTET UNTUK MENINGKATKAN PEMAHAMAN KEBERAGAMAN SENI TRADISI NUSANTARA PADA SISWA SEKOLAH DASAR - Karsono, Karsono; Sujana, Yudianto; Daryanto, Joko; Yustinus, Ngadino (Universitas Pendidikan Indonesia, 2014)
The purpose of this research is to improve the quality of the learning process subjects Culture Art and Skills in elementary school, especially in understanding of the diversity of Indonesian traditional art. This research was conducted in two stages. First, to develop a media card quartet, and second stage is implementation of the themed quartet card into the learning process in the classroom. Research methods use classroom action research approach because the quartet card media was subsequently used in the learning process in the classroom to improve understanding. Source of data collected by conducting interviews, tests, observations, and documentation. The analysis of the data using Miles and Hubberman’s interactive model, includes the step of data reduction, data display, and conclusion. The results showed that the use of card-themed quartet can enhance students' understanding of elementary school SDN 01 Jatisawit and SDN Dilem in the diversity of Indonesian traditional art material.Keywords: instructional media, cards quartet, the diversity of traditional arts.